The Catholic Epistles as a Canonical Janus: A New Testament Glimpse into Old and New Testament Canon Formation - Davids, Peter H. (Bulletin for biblical research, 2009)
The Catholic Epistles look back at the forming "Old Testament" canon, showing not only the use of all segments of the Tanakh but also a preference for the Septuagint, the reading of all Tanakh passages through Second Temple literature, and a wider body of authoritative literature than the Tanakh. They look forward as part of the process of New Testament canon formation in their own use of the Jesus tradition and references to Paul (although references to Pauline literature outside 2 Peter are disputed) and in their own history of canonization in that only one had a smooth acceptance while the others were all ignored or disputed. They were finally accepted as part of a group of seven books, which is the basis of David Nienhuis's novel theory about the creation of James, which may have been viewed as a collection of the three "pillars."